2018
DOI: 10.1007/s12529-018-9756-6
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Refraining from Seeking Medical Care Among Japanese Employees: A 1-Year Prospective Cohort Study

Abstract: BackgroundUsing a 1-year prospective design, we examined the association of organizational justice (i.e., procedural justice and interactional justice) with refraining from seeking medical care (RSMC) among Japanese employees.MethodsWe surveyed 2695 employees (1994 men and 701 women) from two factories of a manufacturing company in Japan. A self-administered questionnaire comprising scales for measuring organizational justice (Organizational Justice Questionnaire) and potential confounders (i.e., demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…This suggests that employees’ interactions with supervisors affect proactive behavior toward workplace–patient coordination and disease treatment among employees with chronic diseases. This result was consistent with previous evidence that showed organizational justice was positively associated with employees’ help-seeking behavior [21, 22]. Trust and mutual respect are important components of interactional justice as expressed in interactions with supervisors, and play a central role in this association [34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that employees’ interactions with supervisors affect proactive behavior toward workplace–patient coordination and disease treatment among employees with chronic diseases. This result was consistent with previous evidence that showed organizational justice was positively associated with employees’ help-seeking behavior [21, 22]. Trust and mutual respect are important components of interactional justice as expressed in interactions with supervisors, and play a central role in this association [34].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study showed that inferences regarding organizational justice also affected the successful implementation of processes to accommodate other employees [20]. A lack of organizational justice has been shown to be positively associated with Japanese employees refraining from seeking medical care [21], whereas organizational justice is positively associated with help-seeking behavior [22]. Organizational justice may be an important factor that influences the decisions of employees with chronic disease regarding reporting their illness to their employer.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Seeking Medical Care. Lack of procedural justice has been associated with refraining from seeking medical care among Japanese employees at one-year follow-up [99].…”
Section: Organizational Justice and Sickness Absence: Longitudinal St...mentioning
confidence: 99%
“…Interactional justice is perceived degree to which one is treated with respect (Inoue, Tsutsumi, Eguchi, & Kawakami, 2019). Among the three forms of justice, distributive justice is highly related to employees' satisfaction with outcomes (i.e.…”
Section: Perceived Fairness Of Performance Appraisalmentioning
confidence: 99%
“…get promoted) and organizational commitment, as they perceived fairness when they think that they received outcomes that they deserved. On the other hand, procedural justice is highly linked to job satisfaction, level of trust, turnover rate and task performance as employees will put efforts to achieve the desired outcomes and were given explanation of why they received the given rates (Inoue et al, 2019). Employees' perceived fairness has a direct impact on the effectiveness of performance appraisal that led to fair perception on performance appraisal system and eventually induces a positive impact on employees' performance in the organization (Zohaib, 2014).…”
Section: Perceived Fairness Of Performance Appraisalmentioning
confidence: 99%